Association of biomarkers of inflammation and HLA-DRB1 gene locus with risk of developing rheumatoid arthritis in females - Klimenta, Biljana; Nefic, Hilada; Prodanovic, Nenad; Jadric, Radivoj; Hukic, Fatima (Rheumatology international, 2019)
Rheumatoid arthritis (RA) is an autoimmune disease causing chronic inflammation of the joints. Multiple factors, including HLA - DRB1 gene variants, influence the susceptibility to RA. The HLA - DRB1 gene is part of a family of genes called the human leukocyte antigen (HLA) complex. In this study, we compared the inflammatory biomarkers values, including erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP), between patients with RA and healthy control group of females of the Public Institution Health Centre of Sarajevo Canton. In addition, we estimated the frequencies of the HLA - DRB1 gene variants and their association with the risk for RA development in females. The haematological and biochemical tests were completed on automated analyzers. To assess the association between the HLA - DRB genes and the risk of RA in females, low-resolution genotyping of the HLA - DRB1 , DRB3, DRB4, and DRB5 gene loci was performed by the sequence-specific polymerase chain reaction method (PCR-SSP). ESR and CRP were the most sensitive acute-phase reactants in females with RA and there was a correlation between ESR and CRP values in RA patients. There was significantly positive association between of the HLA - DRB1 * 03 , * 04 , * 08 , * 10 , * 11, and * 14 variants and elevated values of ESR in RA patients, but negative between HLA - DRB1*03 , * 13 and * 15 alleles and elevated CRP values. Furthermore, our results confirm genetic susceptibility to RA in a female population to the members of the HLA - DRB1*04 and *03 allelic groups, the DRB1*04/DRB1*04 and DRB1*03/DRB1*04 genotypes, and the DRB1*04 - DRB4* or DRB1*03 - DRB3* haplotypes, which, therefore, represent risk factors for the development of this disease. According to our results, the DRB1*01/DRB1*15 and DRB1*07/DRB1*16 genotypes and the HLA - DRB5 gene locus represent a protective factor for RA. The presence of specific HLA - DRB1 gene variants increases the risk of developing RA, while other variants provide protection against disease. Therefore, HLA typing could be helpful in the prediction of RA development and establishing and confirming a definitive diagnosis of autoimmune diseases in some subjects. A strong association with the higher levels of ESR and CRP could be used to establish definitive diagnosis and introduce of early treatment of RA to prevent the occurrence of RA symptoms.